Emerging Governance Architectures in Global Health: Do Metagovernance Norms Explain Inter-Organisational Convergence? - Anna Holzscheiter; Thurid Bahr; Laura Pantzerhielm (Politics and Governance, 2016)
This paper proposes a theoretical account of institutional transformation and the emergence of order in global inter-organisational relations, which is centred on the concept of “metagovernance”. It does so by theorising on the advent of governance architectures in global health governance—relationships between international organisations (IOs) in this field that are stable over time. Global health governance is routinely portrayed as an exceptionally fragmented field of international cooperation with a perceived lack of synergy and choreography between international and transnational organisations. However, our paper starts from the observation that there are also movements of convergence between international organisations. We seek to explain these by looking at the effects of international norms that define good global governance as orderly and harmonised global governance. We conceptualize such norms as “metagovernance norms” that are enacted in reflexive practices which govern and order the relationships between international organisations. Empirically, this paper traces changing interactions and institutional arrangements between IOs (World Health Organization; World Bank; Gavi, the Vaccine Alliance; and the Global Fund to Fight AIDS, Tuberculosis and Malaria) in global health governance since the late 1940s and shows how patterns therein reflect and (re)produce broader discursive perceptions of what “health” is about and how the governance thereof ought to be organised.
Additional information: The publication of this article was funded by the Open Access fund of the Leibniz Association. This article is part of the issue “Supranational Institutions and Governance in an Era of Uncertain Norms”, edited by Russell Alan Williams (Memorial University, Canada) and Reeta Tremblay (University of Victoria, Canada).
Keywords: 330; discourses; global health; international organisations; metagovernance; norms